Siedmiu braci Machabejskich z Czwartej Księgi Machabejskiej jako typ Chrystusa. Próba zastosowania egzegezy typologicznej do tekstu 4 Mch - Baran, Grzegorz Mariusz (Vox Patrum, 2019)
The article presents a kind of attempt of applying typological exegesis to the text of 4 Macc. In the light of the analyzes carried out, it is clear that the seven martyr brothers can be seen as a type of Christ: a number seven, determining number of brothers - the type of perfection of the person of Christ; the origin of the seven brothers from Abraham - the type of origin of Christ; directing by the brothers “pious reason” - the type of surrendering to the Father’s will through Christ; persuasion of Antiochus IV - the type of Christ’s temptation by the devil; the martyr’s sacrifice/victim of the brothers - the type of saving sacrifice of Christ; “established in heaven” brothers - the type of Christ’s ascension. Bearing in mind that 4 Macc drew from 2 Macc or from the same sources, one can state that the manner of presenting the seven brothers by the author of the first century AD, whose history took place in the second century BC, even more - in a typological perspective - brought them closer to the person of Christ. In this context, the mother of seven brothers deserves attention, whose person could be interpreted as a type of Mary - Mother of Christ.